Prototype Telecontrolling Pintu Air Otomatis pada Pengairan Lahan Berbasis Android - Firda Amalia Romana; Moh. Abdullah Anshori; Mochammad Junus (Jurnal Jaringan Telekomunikasi, 2021)
The need for water in each land varies depending on the area and conditions of the land. In addition, the technology is still done manually. We need a lot of time to irrigate the plants therefore it is not effective. Efforts must be made to optimize water management, such as on-time, on quantity, and on target, as well as covering a large area. This research proposes an android-based automatic floodgate telecontrolling system by utilizing a Soil Moisture sensor and an android application. Relays are used as opening and closing sluices. The results of the relay status when on or off and the humidity value will enter the application and can be monitored in real-time. The test results show that the Soil Moisture  Sensor can detect Soil Moisture with an average error of 0.362%. The control and monitoring system through the application using Android is in accordance with the plan with an average delay for ON / OFF status and a humidity value of 0.487295s.